Anthelmintic Activity Test of Pare Leaves Extract (Momordica charantia L.) Against Worms Raillietina sp. by In Vitro - Trifena Pristi Anindyta; Setiawan Koesdarto; Sri Agus Sudjarwo; Lilik Maslachah; mufasirin mufasirin; Nunuk Dyah Retno Lastuti; Lutfiah Annisa Billa (Journal of Parasite Science (JoPS), 2022)
The purpose of this research is to prove that pare leaf extract (Momordica charantia L.) has anthelmintic activity against Raillietina sp. in vitro. This study consisted of four treatments and each treatment contained six replications, each of which consisted of six worms. The treatments in this research were K- with 1% CMC-Na, P1 with 2% extract concentration, P2 with 4% extract concentration, P3 with 8% extract concentration. Pare leaf extract has anthelmintic activity against Raillietina sp. in vitro with an effective dose of 8%. The higher the concentration of pare leaf extract, the higher the mortality rate of worms. The longer the immersion time, the higher the number of dead worms.